American History - Volume 2 - James Maddox Robert (Mc Graw Hill, 2007)
James Maddox Robert, has transformed the facts, figures and dates of American History into a lively and fascinating narrative. The full span of American history is covered, starting with Columbus's landing, then proceeding to colonization, the Revolutionary War against England, the formation of a new government, American growth and expansion during the nineteenth century, and emergence as a major world power in the present century.